Battery modified diaphragm as well as preparation method and application thereof
By constructing a layer-layer assembly structure of MgB2/graphene on the lithium-ion battery separator, the problem of volume expansion of black phosphorus anode material and lithium polyphosphide dissolution shuttle during the lithium embedding process is solved, and the effect of reducing the loss of active substances and improving electrochemical performance is achieved.
Patent Information
- Application Number
- CN202510024104.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
In existing lithium-ion batteries, the volume of black phosphorus negative electrode material expands severely during the lithium embedding process, resulting in increased stress in the electrode, powderization of active substances and collapse of the electrode structure. In addition, during the charging and discharging process, phosphorus forms lithium phosphide, dissolves in the electrolyte, causing a shuttle effect and losing active substances.
By constructing a layer-layer assembly structure of MgB2/graphene on the battery separator, an efficient lithium polyphosphide diffusion barrier layer is formed to prevent the dissolution and shuttle of lithium polyphosphide, reduce the loss of active substance phosphorus, and alleviate the electrode volume changes through the layered structure to stabilize the electrode structure.
It effectively inhibits the volume expansion of the black phosphorus negative electrode material and the dissolution shuttle of lithium polyphosphide, reduces the loss of active substances, improves the electrochemical performance of the black phosphorus negative electrode, and improves the energy density and cycle stability of the battery.
Smart Images

Figure CN119833895A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery diaphragm materials, and in particular relates to a battery modified diaphragm and a preparation method and application thereof. Background Art
[0002] With the rapid development of the new energy industry and the popularization of various portable electronic products, people's demand for today's portable electrochemical energy storage devices has intensified. Battery products with high safety, high energy density and fast charging and discharging have also led a new round of research boom.
[0003] The energy density of existing commercial lithium-ion batteries is limited by the low theoretical specific capacity of positive and negative electrode materials, making it difficult to develop battery products with ultra-high energy density. In particular, the theoretical specific capacity of commercial graphite negative electrodes is only 370mAh / g, which greatly hinders the improvement of battery energy density. To this end, the key to developing batteries with high energy density lies in breaking through the theoretical specific capacity of existing positive and negative electrode active materials. Among them, black phosphorus, as a negative electrode of lithium-ion batteries, exhibits a theoretical specific capacity of up to 2560mAh / g. The layered structure of black phosphorus has good electronic ion conductivity, can achieve large current rapid charging and discharging, and has abundant phosphorus reserves, making it one of the most promising high-energy density battery negative electrode systems. However, black phosphorus negative electrode materials face the same challenges as silicon negative electrodes. During the lithium insertion process, they produce a volume expansion of up to 300%, generate large electrode internal stress, aggravate the pulverization of active materials and the collapse of electrode structure. In addition, during the charging and discharging process, phosphorus will form soluble lithium polyphosphide, which dissolves in ester electrolytes, forming a shuttle effect, causing the loss of active materials and deteriorating the electrochemical performance of the battery.
[0004] Therefore, the key to developing phosphorus negative electrodes is to suppress the volume expansion problem and the dissolution and shuttle problem of polyphosphide during the charge and discharge process. As an important conductive material that blocks the positive and negative electrodes in the battery, the separator directly faces the shuttle path of polyphosphide.
[0005] Therefore, there is a need to provide a new modified battery separator. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a battery modified diaphragm. The battery modified diaphragm suppresses the volume expansion of phosphorus in the electrochemical reaction, blocks the dissolution and shuttle of lithium polyphosphide, reduces the loss of active material phosphorus during the cycle, reduces the capacity decay of the black phosphorus negative electrode, and thus improves the electrochemical performance of the black phosphorus negative electrode.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned battery modified separator.
[0008] The present invention also provides the use of the above-mentioned battery modified diaphragm in a black phosphorus negative electrode lithium battery. In the method, MgB2 and expanded graphite are firstly peeled off in a solvent to obtain a layered structure MgB2 and graphene, and the two layered structures are self-assembled in the solution to obtain a MgB2 / graphene layer-by-layer self-assembled structure dispersion, and then a modified diaphragm is prepared by vacuum filtration for use in a black phosphorus negative electrode.
[0009] In order to achieve the above invention object, the specific technical solution of the present invention is:
[0010] A battery modified diaphragm comprises a base diaphragm and a composite layer attached to the base diaphragm, wherein the composite layer comprises a MgB2 layer and a graphene layer stacked in sequence.
[0011] The side of the battery modified diaphragm with the composite layer faces the black phosphorus electrode.
[0012] The method for preparing the above-mentioned battery modified diaphragm comprises the following steps:
[0013] 1) dispersing MgB2 and expanded graphite powder in an organic solvent to obtain a dispersion;
[0014] 2) subjecting the prepared dispersion to ultrasonic stripping to obtain an ultrasonic stripped solution;
[0015] 3) Using the base membrane as a filter membrane, the solution after ultrasonic stripping is filtered to obtain a membrane with a MgB2 layer and a graphene layer attached;
[0016] 4) Drying the diaphragm with the MgB2 layer and the graphene layer attached thereto to obtain a battery modified diaphragm.
[0017] As a better implementation of the present application, the organic solvent in step 1) is NMP or DMF or a mixture of both, and the mass volume ratio of the mass of the MgB2 and the expanded graphite powder to the mass volume of the organic solvent is 0.01-0.05 g / mL.
[0018] As a preferred embodiment of the present application, in step 1), the mass ratio of MgB2 to expanded graphite is any ratio, and preferably the mass ratio of MgB2 to expanded graphite is 1:1.
[0019] As a preferred embodiment of the present application, the conditions for ultrasonic peeling in step 2) are as follows: ultrasonic power is 400-800 W and time is 1-2 h.
[0020] As a preferred embodiment of the present application, the amount of ultrasonic exfoliation dispersion used in vacuum filtration in step 3) is 0.8-1.5 mL / cm. That is to say, the amount of dispersion used is related to the diameter of the filter membrane. If the diameter of the filter membrane is 5 cm, the volume of ultrasonic exfoliation dispersion used for filtration is 4 ml-7.5 ml.
[0021] As a preferred embodiment of the present application, the base membrane in step 3) includes a polyolefin membrane, a glass fiber membrane and a cellulose membrane.
[0022] As a preferred embodiment of the present application, the drying conditions in step 4) are a drying temperature of 60° C. and a drying time of 12 h.
[0023] As a preferred embodiment of the present application, the step of diluting the ultrasonic exfoliation dispersion liquid is further included before the filtration, and the concentration of the diluted ultrasonic exfoliation dispersion liquid used for the filtration is 0.3-0.8 mg / mL.
[0024] Application of the above-mentioned battery modified separator in black phosphorus negative electrode lithium ion battery.
[0025] In the present application, the battery modified diaphragm prepared by ultrasonic stripping can provide good electronic conductivity and ionic conductivity for the modified layer, and the composite layer on the base diaphragm is a MgB2 / graphene layer-by-layer assembly structure, and the sheet structure of the composite layer can better block the shuttling of lithium polyphosphide and enhance the adsorption and utilization of dissolved lithium polyphosphide. Limiting lithium polyphosphide to the black phosphorus electrode side can effectively prevent the occurrence of the shuttle effect and reduce the loss of active material phosphorus. At the same time, there is a large stress and space gap between the diaphragm and the electrode, which can alleviate the volume change on the electrode, stabilize the electrode structure, and promote electrode stability, thereby improving the electrochemical performance of the black phosphorus negative electrode.
[0026] The battery modified diaphragm prepared by the present invention is a diaphragm surface constructed with a stable barrier layer, which can isolate the diffusion shuttle of dissolved lithium polyphosphide to the lithium electrode and reduce the occurrence of side reactions in the battery; a direct barrier is formed on the diffusion path of lithium polyphosphide through a layered structure to inhibit the migration of active substances to the counter electrode side; the designed MgB2 / graphene layer-by-layer assembly structure modified structure has high ionic conductivity and electronic conductivity, can reuse dissolved lithium polyphosphide, effectively reduce the loss of positive electrode active substance phosphorus, and improve the utilization rate of active substances in electrochemical reactions; at the same time, the modified layer can effectively alleviate the volume change of positive electrode phosphorus during charging and discharging, maintain the stability of the electrode system, and thus improve the electrochemical performance of the black phosphorus negative electrode.
[0027] Compared with the prior art, the positive effects of the present invention are embodied in:
[0028] (i) The battery modified diaphragm of the present invention can improve the electrochemical performance of the black phosphorus negative electrode. By constructing a layer-by-layer assembly structure, an efficient multi-lithium phosphide diffusion barrier layer is formed. The composite layer (MgB2 / graphene layer-by-layer assembly structure) has good electronic conductivity and ionic conductivity, forming an effective upper current collector, improving the utilization rate of active materials, preventing the loss of active materials, and promoting the efficient utilization of multi-soluble lithium phosphides.
[0029] (ii) The layered MgB2 in the composite layer has a high reactivity, which can effectively improve the adsorption effect of carbon materials on lithium polyphosphide and promote the conversion of lithium polyphosphide. By compounding with graphene sheets and having high electronic conductivity, it can promote the electrochemical conversion of phosphorus.
[0030] (III) The battery modified diaphragm has the flexibility of the diaphragm and can act as a buffer layer for the volume change of the phosphorus negative electrode during charge and discharge, inhibiting the volume change, preventing the collapse and breakage of the positive electrode structure during the charge and discharge process, and stabilizing the electrode.
[0031] (IV) Battery modified separators can enhance the electrochemical performance of black phosphorus negative electrodes and improve their practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a SEM image of the MgB2 / graphene layer-by-layer assembly modified diaphragm material prepared in Example 1;
[0033] Figure 2 The SEM image of the MgB2 / graphene layer-by-layer assembly modified diaphragm material prepared in Example 1 and the EDS images of carbon, magnesium and boron elements;
[0034] Figure 3 This is an EDS image of the boron element in the MgB2 / graphene layer-by-layer assembly modified diaphragm material prepared in Example 1;
[0035] Figure 4 This is the EDS image of carbon element in the MgB2 / graphene layer-by-layer assembly modified diaphragm material prepared in Example 1;
[0036] Figure 5 This is the EDS image of the magnesium element in the MgB2 / graphene layer-by-layer assembly modified diaphragm material prepared in Example 1. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0038] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.
[0039] Any feature disclosed in this specification (including claims and abstract), unless otherwise stated, may be replaced by other alternative features that are equivalent or have similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.
[0040] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0041] In this application, the raw materials used are all commercially available products.
[0042] Embodiment 1:
[0043] (1) Weigh 1.0 g of MgB2 and 1.0 g of expanded graphite powder using an electronic balance, transfer 100 mL of NMP (N-methylpyrrolidone) solvent into a beaker, add the weighed powder, add a magnetic stirrer, and continuously stir the sample on a magnetic stirrer to obtain a MgB2 and expanded graphite dispersion.
[0044] (2) The prepared dispersion was transferred to an ultrasonic device, the power was turned on, and the ultrasonic parameters were set to 800 W for ultrasonic power and 2 h for ultrasonic exfoliation to obtain an ultrasonic exfoliation dispersion (MgB2 / graphene layer-by-layer assembly dispersion).
[0045] (3) Take 5 mL of ultrasonic stripping dispersion with a concentration of 0.5 mg / mL, select a filter membrane with a diameter of 5 cm, pass it through a vacuum filtration device, use a lithium-ion battery polyolefin PP diaphragm as a filter membrane, and filter to obtain a modified diaphragm; the 0.5 mg / mL ultrasonic stripping dispersion in this step is obtained by diluting the ultrasonic stripping dispersion in step 2 by adding NMP.
[0046] (4) The modified diaphragm is placed in a vacuum drying oven and dried at a temperature of 60 °C for 12 h to obtain a battery modified diaphragm (MgB2 / graphene layer-by-layer assembled modified diaphragm).
[0047] The modified diaphragm prepared in Example 1 was placed on a plate and cut to obtain a small disc with a diameter of 16 mm. The prepared battery modified diaphragm was assembled into a half-cell with black phosphorus as the negative electrode for 1000 mA / g charge and discharge test. The specific results are shown in Table 1.
[0048] See also Figures 1 to 5 ,from Figure 1It can be seen that the composite layer formed by the sequentially stacked MgB2 layer and the graphene layer is attached to the base diaphragm. Figures 2 to 5 From the element diagram, it can be seen that the diaphragm material includes C, B and Mg elements.
[0049] Embodiment 2:
[0050] (1) Weigh 1.0 g of MgB2 and 4.0 g of expanded graphite powder using an electronic balance, transfer 100 mL of DMF (N,N-dimethylformamide) solvent into a beaker, add the weighed powder, add a magnetic stirrer, and continuously stir the sample on a magnetic stirrer to obtain a MgB2 and expanded graphite dispersion.
[0051] (2) The prepared dispersion was transferred to an ultrasonic device, the power was turned on, and the ultrasonic parameters were set to 800 W for ultrasonic power and 2 h for ultrasonic exfoliation to obtain a MgB2 / graphene layer-by-layer assembly dispersion.
[0052] (3) Take 5 mL of the dispersion after ultrasonic stripping with a concentration of 0.5 mg / mL, select a filter membrane with a diameter of 5 cm, pass it through a vacuum filtration device, use a lithium-ion battery polyolefin PP diaphragm as the filter membrane, and filter to obtain a modified diaphragm.
[0053] (4) The modified diaphragm is placed in a vacuum drying oven and dried at a temperature of 60 °C for 12 h to obtain a MgB2 / graphene layer-by-layer assembled modified diaphragm.
[0054] Similarly, the battery modified diaphragm prepared in Example 2 was placed on a small disc with a diameter of 16 mm. The prepared battery modified diaphragm was assembled into a half-cell with black phosphorus as the negative electrode for 1000 mA / g charge and discharge test. The specific results are shown in Table 1.
[0055] Embodiment 3:
[0056] (1) Weigh 1.0 g MgB2 and 1.0 g expanded graphite powder using an electronic balance, transfer 100 mL NMP solvent into a beaker, add the weighed powder, add a magnetic stirrer, and continuously stir the sample on a magnetic stirrer to obtain a MgB2 and expanded graphite dispersion.
[0057] (2) The prepared dispersion was transferred to an ultrasonic device, the power was turned on, and the ultrasonic parameters were set to 400 W for ultrasonic power and 1 h for ultrasonic exfoliation to obtain a MgB2 / graphene layer-by-layer assembly dispersion.
[0058] (3) Take 5 mL of the dispersion after ultrasonic stripping with a concentration of 0.5 mg / mL, select a filter membrane with a diameter of 5 cm, pass it through a vacuum filtration device, use a lithium-ion battery polyolefin PP diaphragm as the filter membrane, and filter to obtain a modified diaphragm.
[0059] (4) The modified diaphragm is placed in a vacuum drying oven and dried at a temperature of 60 °C for 12 h to obtain a MgB2 / graphene layer-by-layer assembled modified diaphragm.
[0060] The modified diaphragm assembled by layer of MgB2 / graphene was placed on a small disc with a diameter of 16 mm. The prepared modified diaphragm was assembled into a half-cell with black phosphorus as the negative electrode for 1000 mA / g charge and discharge test. The specific results are shown in Table 1.
[0061] Embodiment 4:
[0062] (1) Weigh 4.0 g MgB2 and 1.0 g expanded graphite powder using an electronic balance, transfer 100 mL NMP solvent into a beaker, add the weighed powder, add a magnetic stirrer, and continuously stir the sample on a magnetic stirrer to obtain a MgB2 and expanded graphite dispersion.
[0063] (2) The prepared dispersion was transferred to an ultrasonic device, the power was turned on, and the ultrasonic parameters were set to 600 W for ultrasonic power and 1 h for ultrasonic exfoliation to obtain a MgB2 / graphene layer-by-layer assembly dispersion.
[0064] (3) Take 4 mL of the dispersion after ultrasonic stripping with a concentration of 0.3 mg / mL, select a filter membrane with a diameter of 5 cm, pass it through a vacuum filtration device, use a lithium-ion battery polyolefin PP diaphragm as the filter membrane, and filter to obtain a modified diaphragm.
[0065] (4) The modified diaphragm is placed in a vacuum drying oven and dried at room temperature for 12 h to obtain a MgB2 / graphene layer-by-layer assembled modified diaphragm.
[0066] Embodiment 5:
[0067] (1) Weigh 1.0 g MgB2 and 5.0 g expanded graphite powder using an electronic balance, transfer 100 mL NMP solvent into a beaker, add the weighed powder, add a magnetic stirrer, and continuously stir the sample on a magnetic stirrer to obtain a MgB2 and expanded graphite dispersion.
[0068] (2) The prepared dispersion was transferred to an ultrasonic device, the power was turned on, and the ultrasonic parameters were set to 600 W for ultrasonic power and 1 h for ultrasonic exfoliation to obtain a MgB2 / graphene layer-by-layer assembly dispersion.
[0069] (3) Take 5 mL of the dispersion after ultrasonic stripping with a concentration of 0.8 mg / mL, select a filter membrane with a diameter of 5 cm, pass it through a vacuum filtration device, use a lithium-ion battery polyolefin PP diaphragm as the filter membrane, and filter to obtain a modified diaphragm.
[0070] (4) The modified diaphragm is placed in a vacuum drying oven and dried at a temperature of 40 °C for 12 h to obtain a MgB2 / graphene layer-by-layer assembled modified diaphragm.
[0071] Comparative Example 1:
[0072] (1) Weigh 2.0 g of expanded graphite powder using an electronic balance, transfer 100 mL of NMP solvent into a beaker, add the weighed powder, add a magnetic stirrer, and continuously stir the sample on a magnetic stirrer to obtain an expanded graphite dispersion.
[0073] (2) The prepared dispersion was transferred to an ultrasonic device, the power was turned on, and the ultrasonic parameters were set to 800 W for ultrasonic power and 2 h for ultrasonic exfoliation to obtain a graphene assembly dispersion.
[0074] (3) Take 5 mL of the dispersion after ultrasonic stripping with a concentration of 0.5 mg / mL, select a filter membrane with a diameter of 5 cm, pass it through a vacuum filtration device, use a lithium-ion battery polyolefin PP diaphragm as the filter membrane, and filter to obtain the modified diaphragm.
[0075] (4) The modified diaphragm is placed in a vacuum drying oven and dried at a temperature of 60 °C for 12 h to obtain a graphene-assembled modified diaphragm.
[0076] The modified diaphragm obtained in Comparative Example 1 was placed on a small disc with a diameter of 16 mm. The prepared modified diaphragm was assembled into a half-cell with black phosphorus as the negative electrode for 1000 mA / g charge and discharge test. The specific results are shown in Table 1.
[0077] Comparative Example 2:
[0078] (1) Weigh 2.0 g of MgB2 using an electronic balance, transfer 100 mL of NMP solvent into a beaker, add the weighed powder, add a magnetic stirrer, and continuously stir the sample on a magnetic stirrer to obtain a MgB2 dispersion.
[0079] (2) The prepared dispersion was transferred to an ultrasonic device, the power was turned on, and the ultrasonic parameters were set to 800 W for ultrasonic power and 2 h for ultrasonic time, and ultrasonic exfoliation was performed to obtain a MgB2 assembly dispersion.
[0080] (3) Take 5 mL of the dispersion after ultrasonic stripping with a concentration of 0.5 mg / mL, select a filter membrane with a diameter of 5 cm, pass it through a vacuum filtration device, use a lithium-ion battery polyolefin PP diaphragm as the filter membrane, and filter to obtain a modified diaphragm.
[0081] (4) The modified diaphragm is placed in a vacuum drying oven and dried at a temperature of 60 °C for 12 h to obtain a MgB2 assembled modified diaphragm.
[0082] The modified diaphragm obtained in Comparative Example 2 was placed on a small disc with a diameter of 16 mm. The prepared modified diaphragm was assembled into a half-cell with black phosphorus as the negative electrode for 1000 mA / g charge and discharge test. The specific results are shown in Table 1.
[0083] Table 1 Test results of the prepared black phosphorus negative electrode performance
[0084] It can be seen from the data in Table 1 that the performance of the diaphragm material whose composite layer is the MgB2 layer and the graphene layer is better than the performance of the MgB2 layer and the graphene layer used alone.
[0085] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0086] The parts not described in detail in the present description belong to the known technology in the art. The above embodiments are provided only for the purpose of describing the present invention, and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. Various equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be included within the scope of the present invention.
Claims
1. A battery modified separator, characterized in that: The battery modified diaphragm comprises a base diaphragm and a composite layer attached to the base diaphragm, wherein the composite layer comprises a MgB2 layer and a graphene layer stacked in sequence.
2. The method for preparing the battery modified diaphragm according to claim 1, characterized in that: The following steps are involved: 1) dispersing MgB2 and expanded graphite powder in an organic solvent to obtain a dispersion; 2) subjecting the prepared dispersion to ultrasonic exfoliation to obtain an ultrasonic exfoliation dispersion; 3) Using the base membrane as a filter membrane, the ultrasonic exfoliation dispersion is filtered to obtain a membrane with a MgB2 layer and a graphene layer attached; 4) Drying the diaphragm with the MgB2 layer and the graphene layer attached thereto to obtain a battery modified diaphragm.
3. The preparation method according to claim 2, characterized in that: In step 1), the organic solvent is NMP or DMF or a mixture of the two, and the mass volume ratio of the mass of the MgB2 and the expanded graphite powder to the mass volume of the organic solvent is 0.01-1.5 g / mL.
4. The preparation method according to claim 2, characterized in that: The mixing ratio of MgB2 and expanded graphite in step 1) is arbitrary.
5. The preparation method according to claim 2, characterized in that: The conditions for ultrasonic peeling in step 2) are as follows: ultrasonic power is 400-800 W and time is 1-2 h.
6. The preparation method according to claim 2, characterized in that: The amount of ultrasonic exfoliation dispersion used for vacuum filtration in step 3) is 0.8-1.5 mL / cm.
7. The preparation method according to claim 2, characterized in that: The base membrane in step 3) includes polyolefin membrane, glass fiber membrane and cellulose membrane.
8. The preparation method according to claim 2, characterized in that: In step 4), the drying conditions are as follows: the drying temperature is 20-60°C and the drying time is 1-12 h.
9. The preparation method according to claim 2, characterized in that: The method also includes a step of diluting the ultrasonic exfoliation dispersion before filtration, and the concentration of the diluted ultrasonic exfoliation dispersion used for filtration is 0.3-0.8 mg / mL.
10. Use of the battery modified separator according to claim 1 in a black phosphorus negative electrode lithium ion battery.
Citation Information
Patent Citations
Lithium-sulfur battery
CN109678108A
Preparation method and application of manganese-doped tantalum trisulfide reduced graphene oxide composite material
CN115028162A
Preparation method and application of hydroxylated boron alkene material
CN115385350A
Preparation method of magnesium boride nanosheet and application of magnesium boride nanosheet in Li-S battery diaphragm
CN115465870A